User Experience Game Arknights: Sebuah Penerapan Metode Cognitive Walkthrough - Andri Daviano; Reni Aryani; Daniel Arsa (LPPM Universitas Dinamika Bangsa, 2024)
Every product requires an optimal user experience to ensure user comfort and effective interaction with the product. This research uses the Cognitive Walkthrough method to evaluate the user experience in the Arknights game, a mobile game that won the